Sejarah Kekuasaan di Magelang: Era Klasik hingga Kolonial - Heri Priyatmoko; S.R.L. Aji Sampurno; Fransisca Tjandrasih Adji (LPPM Universitas Putera Batam, 2022)
Magelang was already old, long before the Dutch held the reins. Recorded in a number of inscriptions, Magelang had been favored by Mataram Kuno rulers due to the consideration of its prolific nature and location, in the center of Java. The local term “pakuning tengah pulo Jawa” (nail in the center of Java) is a cultural fact that confirms the geographical position of Magelang. Authority turnover did not make Magelang overturned by rulers. Mataram Islam assigned Magelang as their granary because of its good vegetation due to being surrounded by Mount Merapi, Merbabu, Sumbing, Sindoro, Andong, Ungaran, Telomoyo, and Menoreh. As a negaragung (core area) of Mataram Islam, Magelang had become agricultural product supplier. In 1817, Dutch East Indies government established Kedu as a separate residency. A year later, Magelang was made as the capital of Kedu Residency. In 1906, Magelang was appointed as an autonomous city. In 1926, Magelang gained status of stadsgemeente (town municipality) and had the right to regulate its own domestic. History of authority shows territorial changes in Magelang which adjusts the rulers’ interests from time to time.